Laser engraving and punching of graphene films as flexible all-solid-state planar micro-supercapacitor electrodes. (March 2022) - Zhao, X.; He, D.; You, B.
Abstract: The design of lightweight and flexible micro-supercapacitors (MSCs) to couple with the unprecedented boom of microelectronics is extremely desirable but remains challenging. Herein, a facile and straightforward laser engraving and punching strategy has been reported to fabricate graphene-based planar MSCs with outstanding flexibility, superior modularization and programmable pore generation. The resulting planar flexible MSCs are free of external metal current collectors and separators, and exhibit high specific capacitance, outstanding rate capability and robust stability with 98.4% capacitance retention even after 25, 000 cycles in the PVA/H2 SO4 gel electrolyte. Notably, the output voltage and capacitance of our prepared MSCs are readily adjustable through simple serial and parallel connection, indicative of superior modularization and performance uniformity. Graphical abstract: A facile and straightforward strategy was reported for the fabrication of graphene-based planar micro-supercapacitors (MSCs) by direct laser engraving and punching of high conductive graphene-assembled films (GAFs). The resulting all-solid-state MSCs are flexible and exhibit low resistance, outstanding rate capability and robust stability with 98.1% capacitance retention even after 25, 000 cycles. Image 1